2015
DOI: 10.1002/hep.28109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic hepatitis B virus (HBV) infection in U.S. households: National Health and Nutrition Examination Survey (NHANES), 1988‐2012

Abstract: The number of persons with chronic hepatitis B virus (HBV) infection in the UnitedStates is affected by diminishing numbers of young persons who are susceptible because of universal infant vaccination since 1991, offset by numbers of HBV-infected persons migrating to the United States from endemic countries. The prevalence of HBV infection was determined by serological testing and analysis among noninstitutionalized persons age 6 years and older for: antibody to hepatitis B core antigen (anti-HBc), indicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 19 publications
5
172
3
Order By: Relevance
“…It is estimated that as few as 33% of people with HBV and 54% of people with HCV are aware of their infection status. [4][5][6] • Left undiagnosed and untreated, HBV and HCV can cause liver disease including cirrhosis (scarring of the liver), and liver cancer. 6 • Liver cancer death rates are growing faster than death rates for all other types of cancer.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that as few as 33% of people with HBV and 54% of people with HCV are aware of their infection status. [4][5][6] • Left undiagnosed and untreated, HBV and HCV can cause liver disease including cirrhosis (scarring of the liver), and liver cancer. 6 • Liver cancer death rates are growing faster than death rates for all other types of cancer.…”
Section: Challengesmentioning
confidence: 99%
“…Beginning in 1991, immunization programs for infants and adolescents have resulted in substantial declines in the incidence of HBV infection among young people. 4 HBV is spread in several ways: through sexual contact; sharing needles, syringes, or other drug-injection equipment; from mother to child at the time of birth; in health care settings if equipment such as glucose monitors or supplies are shared; or through incidental household exposures to blood. 13,22,23 HBV is extremely infectious; thus, it is easily transmitted, even in microscopic amounts of blood or body fluids.…”
Section: The Risk For Developing Chronic Infection Is Related To the mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from national US surveys indicated that around 0.9-2.2 million people have chronic HBV infection and 2.7-3.5 million people suffer from chronic HCV infection [30][31][32][33] . Nevertheless, with the implementation of [34] .…”
Section: United Statesmentioning
confidence: 99%
“…Despite increased vaccination rates, chronic HBV prevalence has remained fairly consistent due to immigration of patients from areas of endemicity (5). Treatment of chronic HBV infection has been shown to reduce hepatic fibrosis, reverse cirrhosis, and reduce the development of hepatocellular carcinoma (HCC) (6).…”
mentioning
confidence: 99%